Rethinking China, the Middle East and Asia in a 'Multiplex World' - Keskin, Tugrul,; Mahdavi, Mojtaba, (Social, Economic and Political Studies of the Middle East and Asia ;, 2022)
"This edited volume critically examines the changing dynamics of multidimensional relations between China, Middle East and North Africa (MENA) and Asia in an emerging "multiplex world". It challenges both extremes of "Sinophobia" and "Sinophilia" by studying the real "pragmatist" China. This book, in fifteen chapters, problematizes what MENA and Asia means to China in the age of neoliberalism, explores what are the real or perceived pillars of Sino-MENA-Asia relations, and sheds light on how MENA can benefit from its relations with China while keeping a clear distance from the harms of neoliberal authoritarianism. Contributors are Mojtaba Mahdavi, Tugrul Keskin, Manochehr Dorraj, Sari Hanafi, Habibul Haque Khondker, Dara Conduit, Rigas Arvanitis, Saeed Shafqat, Jordi Quero, Mahesh Ranjan Debata, Andrea Ghiselli, Mher D. Sahakyan, Michael McCall, Yossra M. Taha and Xiaoyue Li"--